Extended and unusual working hours in European companies Establishment Survey on Working Time 2004-2005 - Kummerling, Angelika; Lehndorff, Steffen; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
During the 20th century, extended and unusual or atypical working hours became more and more confined to particular categories of workers in most European countries. This applied, in one way or the other, to all aspects of what may be called 'non-standard hours': the extension of work hours through overtime, working at 'unusual' times beyond traditional societal standards such as the '9 to 5' norm, and varying time schedules over the week, the month or the year, that means 'changing' working hours. For example, night and shift work has become, if for different reasons, the 'natural' way of organising working times for nurses or steelworkers. Over recent years, however, the distinction between those workers exposed to non-standard hours and those who are not appears to have become blurred.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Hours of labor -- European Union countries; Hours of labor -- Economic aspects -- European Union countries; Hours of labor -- European Union countries -- Statistics; Electronic books